Pine wood modification by heat treatment in air - Esteves, Bruno (2012)
Maritime pine (Pinus pinaster) wood has low dimensional stability and durability. Heat treatment was made in an oven using hot air during 2 to 24 h and at 170-200 ºC. A comparison was made against steam heat treatment. The equilibrium moisture content and the dimensional stability (ASE) in radial and tangential directions were evaluated at 35%, 65% and 85% relative humidity. MOE, bending strength and wettability were also determined. At the same mass loss improvements of equilibrium moisture content and dimensional stability were higher for oven heat treatment but the same happened for mechanical strength degradation. A 50% decrease in hemicellulose content led to a similar decrease in bending strength.